Family Dynamics Of Prospective Teachers: A Familial Analysis - et. al., Mrs. M. Sasikala, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study conducted by the investigator is an attempt to investigate the family dynamics of prospective teachers with regard to type of family. A family dynamic is the scheme of family members’ relations and interactions including many prerequisite elements (family arrangements, hierarchies, rules, and patterns of family interactions). Each family is unique in its characteristics; having several helpful and unhelpful dynamics. In this study, the family dynamics consists of cohesion, family communication, family values, family satisfaction and flexibility. Descriptive survey method of research and simple random sampling technique has been employed. Mean, Standard Deviation, and t-test have been used for analyzing the data. The null hypothesis was tested at 5% level of significance. The investigator prepared the questionnaire entitled “Family Dynamics Assessment Scale” and elicited responses from the subjects. Pearson Product Moment (PPM) Correlation Coefficient of 0.87 ascertained the reliability. Based on the percentage analysis result, it is revealed that the level of family dynamics and its dimensions of prospective teachers with regard to type of family was found average and also the‘t’ test reveals that the joint and nuclear families have no effect on the family dynamics of prospective teachers